2000
DOI: 10.1677/joe.0.1640051
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone regulates leptin gene expression in bovine adipose tissue: correlation with adipose IGF-1 expression

Abstract: Leptin, the product of the ob gene, is secreted from white adipocytes and regulates food intake and whole-body energy metabolism. In rodents and humans, leptin gene expression is under complex endocrine and metabolic control, and is strongly influenced by energy balance. Growth hormone (GH) has myriad effects on adipose tissue metabolism. The primary aim of this study was to determine the ability of GH to regulate leptin mRNA expression in bovine adipose tissue in vitro and in vivo. Incubation of subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
2
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 39 publications
9
68
2
4
Order By: Relevance
“…In support of the latter, insulin upregulates leptin expression in vivo and in vitro in rodent and human WAT (Saladin et al 1995, Kolaczynski et al 1996b, Boden et al 1997, and in bovine WAT explants (Houseknecht et al 2000). These effects of insulin are dependent on adequate uptake of glucose, suggesting that cellular energy availability is the primary factor regulating leptin synthesis (Mueller et al 1998, Wellhoener et al 2000.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In support of the latter, insulin upregulates leptin expression in vivo and in vitro in rodent and human WAT (Saladin et al 1995, Kolaczynski et al 1996b, Boden et al 1997, and in bovine WAT explants (Houseknecht et al 2000). These effects of insulin are dependent on adequate uptake of glucose, suggesting that cellular energy availability is the primary factor regulating leptin synthesis (Mueller et al 1998, Wellhoener et al 2000.…”
Section: Discussionmentioning
confidence: 94%
“…Sustained periods of negative EB are also characterized by elevation in the plasma concentration of GH and by GH resistance in the liver, resulting in depressed plasma concentration of IGF-I (McGuire et al 1995, Kobayashi et al 1999. GH attenuates the ability of insulin and dexamethasone to stimulate leptin synthesis in bovine WAT explants (Houseknecht et al 2000), but neither GH nor IGF-I has these effects in rat adipocytes (Hardie et al 1996). Prolactin stimulates leptin synthesis in rats (Gualillo et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this regulation is unknown in ruminant species, but could be due to an increase in the sympathetic nervous system activity in white adipose tissue, as was shown in mice (Trayhurn et al 1998) and is suggested by the negative effect of a beta-agonist infusion on cattle plasma leptin (Chilliard et al 1998a). An alternative explanation could be that the stimulation of leptin expression by insulin (Houseknecht et al 1998a) was decreased during underfeeding. This reduction in leptin production is observed whatever the body fatness of the ewes, which shows that the nutritional status per se could modulate plasma leptin in ruminants, as in monogastric animals.…”
Section: Discussionmentioning
confidence: 99%
“…Wyniki dotychczas opublikowanych prac dotyczących wpływu hormonu wzrostu na sekrecję leptyny są rozbieżne [31][32][33]. W badaniach in vivo przeprowadzonych na różnych gatunkach zwierząt obserwowano zarówno brak wpływu GH na ekspresję leptyny w adipocytach [33], jak i jego działa-nie pobudzające [31] lub hamujące [32].…”
Section: © Copyright By Pteidd 2015unclassified